Ibm Peningkatan Kesadaran Pajak dan Cara Menghitung Pajak Penghasilan Perorangan - Reza Hanafi Lubis; Ratna Sari Dewi; Khairina Taufik (Forum Kerjasama Pendidikan Tinggi, 2021)
The obligations of every citizen in terms of reporting and paying taxes are the same. Every citizen is a tax object for the government. Private taxpayers, whether they are permanent workers or employees or free-duty public servants, are required to calculate the actual tax payable at the end of the year to find out what position the tax payable is. The public must understand how much tax is charged and be aware to pay the tax in accordance with the time specified by the Directorate. General of Taxation (DJP). The location of this devotion is Sekip Village Jalan Pantai Labu, where this village is one of the villages in Kampung Lalang Subdistrict, Deli Serdang Regency, North Sumatra Province. The purpose of community service program activities through PKM (Community Partnership Program) is to increase public understanding and awareness of income tax obtained. The solution that will be done in this IBM Program is socialization to increase knowledge of taxes and awareness to pay taxes. The methods applied are classical and individual. This method of approach is in the form of lectures and practices. The individual approach is carried out during the practice of socializing the calculation of the amount of tax to be paid by small businesses in Sekip Village